(untitled) (Polish Yearbook of International Law, 2023)
The outbreak of the war in Ukraine in 2022 resulted in the revival of long-lasting disagreements in Polish-Russian relations. One aspect concerns numerous Russian properties in Warsaw, many abandoned or used for non-public purposes, and the disparity between both States’ properties in the other in this regard. Although the Polish Government has sought to resolve this matter amicably for many years, ulti- mately several legal proceedings were initiated in Polish courts aimed at recovering some of those premises. Only recently, however, Poland has resolved to employ more decisive steps, including the seizure of the former Soviet residential complex known as Spyville in order to enforce a final judgment. This article sketches the history of the dispute, provides an insight into court proceedings, and discusses the approach of Polish judicial institutions to diplomatic and State immunities.